Internationalisation of high-tech start-ups and fast growth-evidence for UK and Germany - Oliver Bürgel; Andreas Fier; Georg Licht; Gordon Murray (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
For firms acting in technological niches the expansion into foreign markets can be a way to increase sales and to thus to recover initial sunk costs over a shorter time frame. Our research, based on survey data for nearly 600 British and German high-tech start-ups, examines whether internationalisation leads to faster growth among high-tech start-ups. Results show that firms with international sales have higher sales growth than firms that sell only domestically. We find that technological sophistication of products and the experience of entrepreneurs has a positive impact on growth. In addition, intense competition and shorter windows of opportunity increase the pressure to grow rapidly to appropriate the returns from innovation. The findings suggest that high tech firm founders should be more determinedly international in their vision and strategies from the very start of their business to increase the economic success of their efforts.
Keywords: F23; L60; L21; 330; start-ups; high-technology industries; internationalisation; Unternehmensgründung; Hochtechnologiesektor; Unternehmensentwicklung; Multinationales Unternehmen; Internationale Markteintrittsstrategie; Erfolgsfaktor; Schätzung; Großbritannien; Deutschland